ANALYSIS OF THE ACTUAL STATE LUBRICANT TO RESOURCE ELEMENTS CRUSHING AND GRINDING MACHINERY - V. N. Kuznetsova; Ya. V. Yarmovich (Вестник СибАДИ, 2017)
The probabilistic nature of resource allocation units, assembly units and parts of machines and equipment, including crushing and grinding, detects the presence of certain reserves in the improvement of preventive work the system for maintenance and repair. The current stage of improving the maintenance of the machine system includes the development of control actions on the basis of technical diagnostics indicators, which provides the ability to predict the state of machine elements. The article presents the results of studies to determine the needs of crushing and milling equipment to conduct work the system for maintenance or repair based on the actual condition of the lubricant.